1998
DOI: 10.1038/sj.onc.1202224
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Bcl-XS alters cytokinetics and decreases clonogenic survival in K12 rat colon carcinoma cells

Abstract: bcl-XS, a member of the bcl-2 family, has been shown to induce and/or sensitize some cells to undergo programmed cell death, and to negate the anti-apoptotic activity of bcl-XL and bcl-2 by mechanisms which are still uncertain. To help understand these mechanisms we have established stable derivatives of the K12 rat colon carcinoma cell line that express bcl-XS in a tetracyclineregulated manner, using an autoregulatory retroviral cassette. When bcl-XS expression is induced, we observe two phenotypic responses.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

1999
1999
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 18 publications
1
9
0
Order By: Relevance
“…Using an antisense mRNA approach in murine embryos, we observed that the classical Bcl-xL isoform is not required for progression of eightcell embryos through the blastocyst stage. In contrast, upregulation of the alternative splicing form Bcl-xS renders blastomeres more susceptible to death and cell cycle arrest , as previously observed in other cell types (Fridman et al 1998, Lindenboim et al 2000, suggesting that this gene may be an important component of the regulation of embryonic fate. Among other anti-apoptotic Bcl-2 family members, Bcl-w and Bfl-1/A1 are only weakly and inconsistently expressed (Jurisicova et al 1998a, Metcalfe et al 2004) and thus are unlikely to play a part in regulating early embryo demise.…”
Section: Anti-apoptotic Bcl-2 Family Membersmentioning
confidence: 73%
“…Using an antisense mRNA approach in murine embryos, we observed that the classical Bcl-xL isoform is not required for progression of eightcell embryos through the blastocyst stage. In contrast, upregulation of the alternative splicing form Bcl-xS renders blastomeres more susceptible to death and cell cycle arrest , as previously observed in other cell types (Fridman et al 1998, Lindenboim et al 2000, suggesting that this gene may be an important component of the regulation of embryonic fate. Among other anti-apoptotic Bcl-2 family members, Bcl-w and Bfl-1/A1 are only weakly and inconsistently expressed (Jurisicova et al 1998a, Metcalfe et al 2004) and thus are unlikely to play a part in regulating early embryo demise.…”
Section: Anti-apoptotic Bcl-2 Family Membersmentioning
confidence: 73%
“…Several studies have demonstrated that Bcl-X S expression enhances the sensitivity and apoptosis of cancer cells in response to chemotherapeutic agents (8)(9)(10). The effect of Bcl-X S expression on cell survival has also been assessed in both in vivo animal tumor models (25) and in vitro clonogenic survival assays (15). These studies have provided strong evidence for the role Bcl-X S in apoptosis and chemosensitization.…”
Section: Discussionmentioning
confidence: 97%
“…In contrast to previous studies, we have employed a tetracycline-regulated expression system to evaluate the effect of Bcl-X S expression on radiation survival. Initial studies carried out in this system showed that Bcl-X S expression induced rapid cell death in NIH 3T3 fibroblasts and reduced clonogenic survival in rat colon carcinoma cells (15,16). Bcl-X S -induced cell death occurred independent of caspase activation and was associated with cytochrome c depletion and loss of mitochondrial membrane potential (16,17).…”
Section: Introductionmentioning
confidence: 98%
“…Thus, RUNX2 knockdown resulted in upregulation of gene nodes/genes known to be implicated in apoptosis induction or displaying TSG functions (see Figure 7A). Notably the UBC interaction network and its members were shown to decrease in anchorage-independent cell growth and increase apoptosis, suggesting UBC may act as a negative regulator of skin carcinogenesis [48]; CRYAB has been reported as a potential TSG [49], while increased expression of BCL-XS (BCL2L1) protein in tumors was associated with decreased proliferation and induction of apoptosis [50], [51]. Similarly, CTGF upregulation was found to be associated with apoptosis and decrease of tumor cell invasion [52][54]; PPM1A (PP2C) expression could induce cell cycle arrest and apoptosis via activation of the p53 pathway [55], and NF2 has been characterized as a TSG in different cancers [56][58].…”
Section: Discussionmentioning
confidence: 99%